Strategi Digital UMKM: Meningkatkan Keberlangsungan Usaha di Era E-Commerce - Widiastuti, C Tri; Setiawan, David Firna; Sumastuti, Efriyani; Ainiyah, Musﬁrotul; Saputra, Rizqi Dian; Dhani, Putri Rahma (Universitas Pahlawan Tuanku Tambusai, 2025)
Business actors in Bengkle Hamlet struggle to sell and introduce their products, even though they are of superior quality due to plentiful natural resources. The key challenges include restricted marketing tactics, market access, and insufficient digital technology and promotion utilization. Education, training, and mentoring on digital marketing and e-commerce optimization are provided to address this. This activity includes practical tasks to assist participants in developing their theoretical understanding, solving challenges, and receiving additional coaching as needed. The community service program has five stages: socialization, education and training, science and technology use, pre- and post-test evaluation, and sustainability. The exercise resulted in a 79.26% improvement in participants' understanding of e-commerce, indicating that they can understand and implement the information effectively in their digital marketing activities.